Mister Exam

Other calculators

Integral of x*exp(-(x/2)) dx

Limits of integration:

from to
v

The graph:

from to

Piecewise:

The solution

You have entered [src]
  1          
  /          
 |           
 |     -x    
 |     ---   
 |      2    
 |  x*e    dx
 |           
/            
-1           
11xex2dx\int\limits_{-1}^{1} x e^{- \frac{x}{2}}\, dx
Integral(x*exp(-x/2), (x, -1, 1))
Detail solution
  1. Use integration by parts:

    udv=uvvdu\int \operatorname{u} \operatorname{dv} = \operatorname{u}\operatorname{v} - \int \operatorname{v} \operatorname{du}

    Let u(x)=xu{\left(x \right)} = x and let dv(x)=ex2\operatorname{dv}{\left(x \right)} = e^{- \frac{x}{2}}.

    Then du(x)=1\operatorname{du}{\left(x \right)} = 1.

    To find v(x)v{\left(x \right)}:

    1. Let u=x2u = - \frac{x}{2}.

      Then let du=dx2du = - \frac{dx}{2} and substitute 2du- 2 du:

      (2eu)du\int \left(- 2 e^{u}\right)\, du

      1. The integral of a constant times a function is the constant times the integral of the function:

        False\text{False}

        1. The integral of the exponential function is itself.

          eudu=eu\int e^{u}\, du = e^{u}

        So, the result is: 2eu- 2 e^{u}

      Now substitute uu back in:

      2ex2- 2 e^{- \frac{x}{2}}

    Now evaluate the sub-integral.

  2. The integral of a constant times a function is the constant times the integral of the function:

    (2ex2)dx=2ex2dx\int \left(- 2 e^{- \frac{x}{2}}\right)\, dx = - 2 \int e^{- \frac{x}{2}}\, dx

    1. Let u=x2u = - \frac{x}{2}.

      Then let du=dx2du = - \frac{dx}{2} and substitute 2du- 2 du:

      (2eu)du\int \left(- 2 e^{u}\right)\, du

      1. The integral of a constant times a function is the constant times the integral of the function:

        False\text{False}

        1. The integral of the exponential function is itself.

          eudu=eu\int e^{u}\, du = e^{u}

        So, the result is: 2eu- 2 e^{u}

      Now substitute uu back in:

      2ex2- 2 e^{- \frac{x}{2}}

    So, the result is: 4ex24 e^{- \frac{x}{2}}

  3. Now simplify:

    (2x+4)ex2- \left(2 x + 4\right) e^{- \frac{x}{2}}

  4. Add the constant of integration:

    (2x+4)ex2+constant- \left(2 x + 4\right) e^{- \frac{x}{2}}+ \mathrm{constant}


The answer is:

(2x+4)ex2+constant- \left(2 x + 4\right) e^{- \frac{x}{2}}+ \mathrm{constant}

The answer (Indefinite) [src]
  /                                 
 |                                  
 |    -x              -x         -x 
 |    ---             ---        ---
 |     2               2          2 
 | x*e    dx = C - 4*e    - 2*x*e   
 |                                  
/                                   
xex2dx=C2xex24ex2\int x e^{- \frac{x}{2}}\, dx = C - 2 x e^{- \frac{x}{2}} - 4 e^{- \frac{x}{2}}
The graph
-1.0-0.8-0.6-0.4-0.21.00.00.20.40.60.85-5
The answer [src]
     -1/2      1/2
- 6*e     + 2*e   
6e12+2e12- \frac{6}{e^{\frac{1}{2}}} + 2 e^{\frac{1}{2}}
=
=
     -1/2      1/2
- 6*e     + 2*e   
6e12+2e12- \frac{6}{e^{\frac{1}{2}}} + 2 e^{\frac{1}{2}}
-6*exp(-1/2) + 2*exp(1/2)
Numerical answer [src]
-0.341741416875544
-0.341741416875544

    Use the examples entering the upper and lower limits of integration.